Evaluation of the possibility of using domestic flavoring and aromatic compounds in the production of beer drinks - Karpenko D. V.; Moiseyak M. B.; Lyalina M. S.; Panesh M. K.; Annagulyyeva M.; Voropaeva A. S. (Vestnik MGTU)
In the technology of beer drinks it is possible to use flavoring raw materials introduced before the start of the main fermentation. The study has shown the feasibility of preparing wort for obtaining beer drinks with the coffee concentrate "Ethiopia Sidamo" or raspberry juice with the replacement of 40 % of light barley brewing malt with unmalted barley, preliminary mashing of barley and the use of the enzyme preparation "Ceremix Plus MG". The implementation of this method provides acceptable characteristics of beer wort. The use of the enzyme preparation Pectinex Yieldmash Plus in a dosage of 120 cm3/t of berries and processing time of 60 minutes contribute to the intensification of the extraction of target components from raspberries: the volume of juice increased by 21.5 %, the concentration of reducing substances – by 65, dry substances – by 4, color intensity – by 14, the yield of dry substances – by 26 %. The content of ethyl alcohol and actual extract in the samples of fermented unfiltered beer drinks has been experimentally established: without the addition of flavoring ingredients – 4.95 and 3.85 wt.%, with raspberry juice – 5.32 and 3.84, coffee extract – 3.54 and 4.89 wt.%. According to the organoleptic assessment, the experimental samples have had an intense color characteristic of the raw materials used; the coffee extract has provided the aroma of coffee, but the taste of the drink as well as the taste and aroma of the beer drink with raspberry juice, have been poorly expressed. In the course of further research, it is necessary to determine the rational moment for introducing flavoring components into the technological process: before the start of the main fermentation or after the end of secondary fermentation and maturation.